The construction of a corporate dictionary for the needs of the dynamic business process management - Stępniak, Cezary (Konstrukcja słowników korporacyjnych na potrzeby dynamicznego zarządzania procesami biznesowymi, 2018)
The article discusses the issue of corporate dictionaries that can be used for the dynamic management of business processes. The article indicates that dictionaries can be used for a full description of business process models. In these full descriptions, various types of ontologies are included relating to various aspects of organization management. These include ontologies describing the types of operations available, actors and their competences, documentation and their content, including the division into information fields and, in the case of unstructured documents, also tags and key words, resource classifications and performance indicators (PPI - Process Performance Indicators). By binding these types of ontologies, one can create a tool that will support ongoing business process management at various levels: individual operations, process instances, and even types and versions of processes. These dictionaries can communicate various IT tools such as ERP / BI class systems, as well as IT tools available on the Internet and supporting business partners of a given organization
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 4 (50), s. 148-159
Keywords: corporate dictionary; ontologies; dynamic process management; life cycle of processes; full description of process models; słownik korporacyjny; ontologie; dynamiczne zarządzanie procesami; fazy życia procesów; pełny opis modeli procesów